"Does the use of gestation-specific centiles for cervical length change the management of pregnancies at risk of recurrent spontaneous preterm birth?". (September 2021) - O'Reilly, Pauric; Dakin, Alex; Keating, Niamh; Luethe, Larissa; Corcoran, Siobhan
Abstract: Introduction: Preterm birth is the leading cause of neonatal morbidity and mortality. Spontaneous Preterm Birth (sPTB) has many and varied causes but is known to be strongly associated with a short or shortening cervix in the midtrimester of pregnancy. The strongest risk factor for sPTB is a previous sPTB. In women with a history of sPTB, we can offer surveillance and treatments which have been proven to reduce the risk of sPTB, such as cervical cerclage and vaginal progesterone supplementation. Alongside other indications, we currently use 25 mm or shorter as a "trigger threshold" for offering cervical cerclage treatment in the Preterm Birth Prevention Clinic at The National Maternity Hospital. Aim: To determine if using gestation-specific centiles instead of a 25 mm cut-off for cervical length changes the antenatal management of women at high risk of sPTB. Method: This was a retrospective chart review of all women attending the preterm birth clinic over the 2-year period 2018–2020 in a large tertiary referral unit in Dublin, Ireland. Demographic details, obstetric history, preterm birth risk factors and preventative treatments offered were collected and analysed. Cervical lengths were measured with ultrasound using a standardised protocol and all performed or supervised by 2 experienced sonographers. Results: A total of 200 patients with known risk factors for sPTB attended the Preterm Birth Surveillance Clinic at the National Maternity Hospital during the study period. Of these, 36/200 (18%) went on to deliver again prior to 37 weeks despite attending the clinic +/- receiving interventions & this group are the focus of this paper. The indications for surveillance in this group that had a recurrent sPTB included recurrent second-trimester pregnancy losses/preterm delivery < 34 weeks (26/36 (72%)), cervical trauma (including treatment of CIN) (12/36 (33%)), congenital abnormalities (1/36 (2.8%)), uterine anomaly (1/36 (2.8%)) and placental bleeding (1/36 (2.8%)). There was one smoker in this series. Funnelling was observed in 3/36 cases (8.3%). Of the 36 patients, an additional 15 would have received a cerclage had gestation-specific centiles, i.e., <5th centile, been used and an additional 10/36 (28%) would have been offered progesterone therapy. Conclusion: In those at high risk of preterm birth, the use of gestation-specific centiles for cervical length increases the proportion of patients that would be eligible for cervical cerclage. It is unclear whether this would change clinical outcome.